Setting population targets for mammals using body mass as a predictor of population persistence - Hilbers, Jelle P (Conservation biology : the journal of the Society for Conservation Biology, 2017)
© 2016 The Authors. Conservation Biology published by Wiley Periodicals, Inc. on behalf of Society for Conservation Biology.